Biography as Compilation: How to Encode Georg Nikolaus Nissen’s Biographie W. A. Mozart’s (1828) in TEI P5 - Anja Morgenstern (OpenEdition, 2020)
The project of editing the early Biographie W. A. Mozart’s (1828) by Georg Nikolaus Nissen (Nissen Online) began as part of the Digital Mozart-Edition (DME) at the Mozarteum Foundation Salzburg. The aim of the edition is to reveal the structure of the text by identifying the diverse sources Nissen relied on when writing the biography. These include primary sources such as original letters and documents from the Mozart family, secondary sources such as contemporary literature about Wolfgang Amadeus Mozart, and original text written by the author and later editors. Considering the challenges that arise when creating an edition that tries to define the different strands of a text, this paper describes how XML/TEI markup was applied to encode text passages which often do not correlate with common text structures (paragraphs, chapters); document different types of sources and their authors or editors; and integrate a detailed bibliography of the sources as well as critical annotations for each single text passage.